Penggunaan Aplikasi Virtual Private Network pada Situs Internet Terblokir (Studi Komparatif Hukum Islam dan Hukum Positif) - Khoirul Anwar; Imran Muhammad Yunus; Ariesman Ariesman (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This research aims to find out and understand the description of the practice of using VPN on blocked internet sites and how Islamic Law and Positive Law view the use of VPN on blocked internet sites. This research uses a type of qualitative descriptive research (non-statistical), which focuses on the study of manuscripts and texts, using a normative juridical approach method and supported by a comparative approach method and using descriptive analysis methods. The research results found are as follows: first, VPN is an application created with the aim of securing computer network systems and data traffic. The way VPN works is to change the IP/Internet Protocol of a device connected to the internet, to a random IP. With this function, VPN can be misused as a means to access sites blocked by the Indonesian government, such as pornography, gambling and violence sites. Second, referring to the Al-Qur'an, Hadith, and Islamic jurisprudence rules that the original law of VPN is permissible. However, misuse of VPN to access sites blocked by the government is prohibited. His actions are categorized as immoral, and the government can impose punishments on perpetrators of VPN misuse. Third, there are no specific laws/regulations in Indonesia that regulate VPNs, however misuse of VPNs to access sites blocked by the government is a criminal act that can be subject to sanctions, the form of punishment is regulated in the ITE Law no. 19 of 2016 Article 45.